2022
DOI: 10.3390/ijms23063086
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Genomic Tools in Plant Breeding: Crop Biofortification

Abstract: Crop breeding has mainly been focused on increasing productivity, either directly or by decreasing the losses caused by biotic and abiotic stresses (that is, incorporating resistance to diseases and enhancing tolerance to adverse conditions, respectively). Quite the opposite, little attention has been paid to improve the nutritional value of crops. It has not been until recently that crop biofortification has become an objective within breeding programs, through either conventional methods or genetic engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 231 publications
(301 reference statements)
0
5
0
Order By: Relevance
“…Frank et al ( 125 ) found that the peroxide content in the Arabidopsis thaliana SSADH mutant was increased and the growth development was affected, which could be associated the accumulation of SSA and GHB. According to a study focusing on GABA-T-SSADH coupling activity of the GabT-GabD protein, NCgl2515 participated in the catabolism and utilization of GABA with GABA-T activity except for GabT in Corynebacterium glutamicum ( 126 ).…”
Section: Anabolism and Catabolism Of Gabamentioning
confidence: 99%
“…Frank et al ( 125 ) found that the peroxide content in the Arabidopsis thaliana SSADH mutant was increased and the growth development was affected, which could be associated the accumulation of SSA and GHB. According to a study focusing on GABA-T-SSADH coupling activity of the GabT-GabD protein, NCgl2515 participated in the catabolism and utilization of GABA with GABA-T activity except for GabT in Corynebacterium glutamicum ( 126 ).…”
Section: Anabolism and Catabolism Of Gabamentioning
confidence: 99%
“…Over the past decades, one of the most promising breeding trends has been biofortification (a strategy to improve the nutritional quality of cultivated plants by breeding methods using a number of biotechnologies) aimed at enriching the edible parts of the plant with micronutrients (vitamins, minerals and trace elements) (Medina-Lozano, Díaz, 2022). This approach, combined with molecular methods for identifying parental forms and analyzing hybrid progeny, has made it possible to obtain a large number of high-yielding varieties and hybrids of crops, including maize hybrids with a high content of provitamin A (Pixley et al, 2013;Muthusamy et al, 2014;Liu et al, 2015;Menkir et al, 2017;Prasanna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…That is the space in which corporations have operated, but academics have devoted considerable attention to output traits, the characteristics of the food produced, for example fortification of edible portions of plants with heightened levels of certain vitamins 395 and other nutrients. 396 Some modifications have exploited the advantages of expression in plastids, though primarily in tobacco. 385 One application is the long sought but ephemeral goal of edible vaccines, 397,398 particularly relevant in developing countries, where conventional vaccination faces economic and practical barriers.…”
Section: Iiic3 Expression Within Neoplasts Of Neoplast-localized Gene...mentioning
confidence: 99%
“…The process is made much more efficient by marker-assisted (or genomic-assisted) breeding, in which the presence of the desired trait is determined molecularly at the seedling stage. 396,434,435 However, even with six sequential backcrosses (which could entail multiple years), hundreds of genes from the wild strain would likely remain. 436 Furthermore, crosses are not possible when introducing desirable wild genes into cultivars such as apple, which are propagated asexually, without destroying the cultivar's distinctive qualities.…”
Section: Iiic4b Neoplasts Specialized For Different Types Of Nuclear ...mentioning
confidence: 99%